Degradation of Oxirane Ring for Epoxidation of Palm Oleic Acid via In Situ Performic Acid - Azmi, Intan S.; Wahi, Nurul Fathia; Jalil, Mohd Jumain (Recent Innovations in Chemical Engineering, 2022)
Background: The world’s raw material consumption has shifted from the use nonrenewable materials to renewable materials. Methods: In this study, the epoxidation of palm oleic acid was carried out by in situ performic acid to produce epoxidized palm oleic acid. Since the epoxide ring is highly reactive, the degradation of the oxirane was examined by using hydrogen peroxide, formic acid, and water. Results: A mathematical model was developed by using the numerical integration of the 4th order Runge-Kutta method and the results showed that there is a good agreement between the simulation and experimental data, validating the kinetic model. As a result, the degradation is highly effective in acidic conditions such as hydrogen peroxide and formic acid, which leads to the formation of side products such as diol and α-glycol. The kinetic rate (k) parameters obtained by using ode45 function in MATLAB software is k11= 6.6442, k12= 7.0185, k2= 0.1026, for epoxidation of palm oleic acid, and k3 = 0.0347, k4= 0.0154, k5= 0.142, in degradation process. Conclusion: The minimum error of the simulation is 0.17311.
Keywords: optimization